The impact of computerization on the reference library staff of four university libraries in Metro Manila - Ontiveros, Irene P. (1998)
The purpose of this study is to assess the impact of computerization specifically on the reference library staff of four university libraries in Metro Manila, i.e., UP Diliman Main Library, Ateneo de Manila University Library, De La Salle University Library and University of Santo Tomas Library. The impact assessment method developed by the International Development Research Centre (IDRC) was used. However, only three out of five IDRC assessment indicators were used, i.e., performance, effectiveness and impact. Twenty-six library staff of the four university libraries responded to a structured questionnaire.